The analysis of total suspended particles (tsp) emitted by the motor vehicle in an urban areas: Kuala Terengganu case study. - Yahaya, Noor Zaitun; Mohd. Sadullah, Ahmad Farhan (2006)
The Total Suspended Particles (TSP) concentration levels were measured at a road kurbside in selected areas in Kuala Terengganu City. The aim of this study is to develop a mathematical equation between TSP and meteorological parameters. The objective is to determine the most significant parameters influenced the TSP levels in an urban area. The sampling areas were characterized into an open and enclosed area which based on the distance to the nearest structures nearby and were representing an idling mode of the motor vehicles movements. The results indicate that the mean for TSP is significantly higher in an open spaced, which is 120 Âµg/m3 compared to 89 Âµg/m3 in an idling enclosed area. It were indicated in this study that high correlation between TSP levels and meteorological parameters namely humidity, temperature and wind speed were higher in an enclosed areas which is more than 0.60 compared to an opened areas which indicates approximately about 0.53. The buildings surroundings and the motor vehicles were found influenced the concentration of pollutant. The coefficient of determination value of the model developed were found more than 0.5 which indicate that the adopt method of analysis in analyzing and predicting the air pollution data were accepted.